Respuesta :
Given:
The polynomial [tex]x^3-1[/tex] is divided by (x+2).
To find:
The remainder.
Solution:
Remainder theorem: If a polynomial p(x) is divided by (x-c), then the remainder is p(c).
Consider the polynomial:
[tex]p(x)=x^3-1[/tex]
It is divided by (x+2). So, by the remainder theorem the remainder is p(-2).
Substituting x=-2 in the above polynomial, we get
[tex]p(-2)=(-2)^3-1[/tex]
[tex]p(-2)=-8-1[/tex]
[tex]p(-2)=-9[/tex]
Therefore, the remainder is -9.
The remainder when x³ - 1 is divided by (x + 2) is -9
Polynomial is an expression consisting of only the operations of addition, subtraction, multiplication of variables.
The remainder theorem states that when a polynomial f(x), is divided by a linear polynomial x - a, the remainder of that division will be equivalent to f(a).
Given the polynomial f(x) = x³ - 1.
The linear equation is x + 2, hence; x = -2
f(-2) = (-2)³ - 1 = -8 - 1 = -9
The remainder when x³ - 1 is divided by (x + 2) is -9
Find out more at: https://brainly.com/question/13416073